An Alternative to Current Therapies of Functional Dyspepsia: Self-Administrated Transcutaneous Electroacupuncture Improves Dyspeptic Symptoms. (30th October 2014) - Ji, Ting; Li, Xueliang; Lin, Lin; Jiang, Liuqin; Wang, Meifeng; Zhou, Xiaopin; Zhang, Ranran; Chen, Jiande DZ
Abstract : Functional dyspepsia is of high prevalence with little treatment options. The aim of this study was to develop a new treatment method using self-management transcutaneous electroacupuncture (TEA) for functional dyspepsia (FD). Twenty-eight patients with FD were enrolled and underwent a crossover clinical trial with 2-week TEA at ST36 and PC6 and 2-week sham-TEA at nonacupuncture sham-points. Questionnaires were used to assess symptoms of dyspepsia and quality of life. Physiological testing included gastric emptying and electrogastrography. It was found that (1) TEA but not sham-TEA significantly improved dyspeptic symptoms and 4 domains in quality of life; improvement was also noted in self-rated anxiety and depression scores; (2) gastric emptying was significantly and substantially increased with 2-week TEA but not sham-TEA; and (3) gastric accommodation was also improved with TEA but not sham-TEA, reflected as increased ingested nutrient volumes at the levels of satiety and maximum tolerance. These findings suggest a therapeutic potential of self-administrated TEA method for functional dyspepsia, possibly attributed to improvement in gastric motility.